Pembinaan Terhadap Narapidana Pengguna Narkotika Di Lembaga Pemasyarakatan Narkotika Kelas II A Jakarta - Dewi Linarsih; Muhammad Khemal Andhika (Widya Yuridika, 2021)
Law in Indonesia is now developing following a variety of human needs. The development of this law was also followed by the development of the prison system into a correctional system based on Pancasila and the 1945 Constitution. The change was made because the prison system only prioritizes the element of revenge and imprisonment only, so that the human rights of inmates are not taken into account. The type of research used in this study is a descriptive type of research. Based on the research that has been conducted the Implementation of Inmate Development in Narcotics Correctional Institution Class IIA Jakarta The implementation of coaching of inmates is stipulated in Article 7 of Government Regulation No. 31 of 1999 concerning The Construction and Mentoring of Community Correctional Officers.